Penerapan Media Postcard untuk Meningkatkan Keaktifan Siswa SMK Ma’arif NU Kajen Tahun 2021/2022 - Yudharina Fitria Kemalasari (Universitas Palan, 2024)
The learning model applied during the COVID-19 pandemic has changed the way students learn, so that student activity in the learning process in class is still low and there are many student absences after the pandemic. Almost 2 years of the pandemic have required students to study from their respective homes so that students are increasingly lazy or less active in learning. This is the basis for the idea of ​​how to make them more effective in learning by using postcard media. Postcard media is a media containing questions related to learning that must be answered by students by taking lucky coupons. The purpose of this study is 1) To describe the teacher's process in implementing postcard media in building student activity in learning in class XI of SMK Ma'arif NU Kajen. 2) To analyze the level of student activity of class XI of SMK Ma'arif NU Kajen through the application of postcard media in learning. This classroom action research was conducted at SMK Ma'arif NU Kajen with the research subjects of class XI students totaling 72 students with almost the same academic abilities, able to understand simple materials, but the level of student activity is low, the majority are less brave in expressing ideas, ideas and opinions. Data collection techniques include questionnaire sheets and documentation. Data analysis used is qualitative and quantitative data analysis. The results of the study showed that the process of implementing postcard media which was carried out through three stages, namely the process of designing a learning plan, the process of implementing learning, and the process of evaluating the use of learning media has been implemented well by teachers. In cycle I, the results of the questionnaire showed that the application of postcard media to increase student activity was successful with an average score reaching 86%. In cycle II, the application of postcard media to increase student activity was successful with an average questionnaire score reaching 88%. Postcard media has proven to be effective in increasing student activity in learning. For teachers, it is expected to be able to improve learning media so that students can be encouraged to be active in class. For schools, it is expected to be able to provide adequate facilities, especially the provision of teaching aids so that teachers can be more free in creating a creative learning process.